Epistemologi Empiris Qur’ani: Kajian Tafsir Tematik atas QS. Āli ‘Imrān [3]: 190-191, al-Ḥujurāt [49]: 6, dan al-Mulk [67]: 3-4 - Anas Kholik; Ahmad Zain Sarnoto (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
The study of empirical verses in the Qur’an has gained renewed significance in the context of twenty-first–century scientific advancement, digital transformation, and the rapid circulation of information. Although discussions on the integration of science and religion have grown within Islamic philosophy and contemporary epistemology, many of these works exhibit a fundamental gap: the Qur’anic text itself is not analyzed as the primary object of study. Instead, empirical verses are often cited as slogans to support the discourse of “Islamic scientific ethics” or “integrative epistemology,” without undergoing rigorous tafsir-based examination. This research fills that gap by Conducting a thematic exegesis of three foundational empirical verses: Āli ‘Imrān [3]:190–191, which emphasizes cosmic contemplation (tadabbur); al-Ḥujurāt [49]:6, which establishes the principle of verification (tabayyun); and al-Mulk [67]:3–4, which introduces the principle of repeated observation (takrār al-baṣar). Employing the tafsīr mawḍū‘ī (thematic exegesis) method, this study integrates linguistic analysis, semantic mapping, contextual background, and a comparative reading of classical and contemporary commentaries. The findings reveal that these three verses collectively construct a Qur’anic empirical epistemology founded on three pillars: reflective observation (tadabbur), verification of information (tabayyun), and repeated examination (takrār al-baṣar). Together, they offer not only a Qur’anic articulation of empirical reasoning but also a value-laden framework in which empirical inquiry is guided by spiritual awareness and ethical responsibility. This research contributes to Qur’anic studies by grounding the discourse of empiricism and epistemology in the text itself rather than in philosophical abstraction. The proposed model provides a conceptual foundation for developing research methodology, scientific ethics, and Islamic education that are firmly rooted in the Qur’anic worldview.